Frailty as Tested by Gait Speed is an Independent Risk Factor for Cirrhosis Complications that Require Hospitalization. (December 2016) - Dunn, Michael A; Josbeno, Deborah A; Tevar, Amit D; Rachakonda, Vikrant; Ganesh, Swaytha R; Schmotzer, Amy R; Kallenborn, Elizabeth A; Behari, Jaideep; Landsittel, Douglas P; DiMartini, Andrea F; Delitto, Anthony
Abstract : Objectives: Frailty is a known risk factor for major life‐threatening liver transplant complications, deaths, and waitlist attrition. Whether frailty indicates risk for adverse outcomes in cirrhosis short of lethality is not well defined. We hypothesized that clinical measurements of frailty using gait speed and grip strength would indicate the risk of subsequent hospitalization for the complications of cirrhosis. Methods: We assessed frailty as gait speed and grip strength in a 1‐year prospective study of 373 cirrhotic patients evaluated for or awaiting liver transplantation. We determined its association with the outcome of subsequent hospital days/100 days at risk for 7 major complications of cirrhosis. We tested potential covariate influences of Model for Endstage Liver Disease (MELD) and Child–Turcotte–Pugh (CTP) scores, age, sex, height, depression, narcotic use, vitamin D deficiency, and hepatocellular carcinoma using multivariable modeling. Results: Patients experienced 2.14 hospital days/100 days at risk, or 7.81 days/year. Frailty measured by gait speed was a strong risk factor for hospitalization for all cirrhosis complications. Each 0.1 m/s gait speed decrease was associated with 22% greater hospital days ( P <0.001). Grip strength showed a similar but nonsignificant association. Gait speed remained independently significant when adjusted for MELD, CTP, and other covariates. At hospital costs of $4, 000/day, patients with normal 1 m/s gait speed spent 6.2 days and $24, 800/year; patients with 0.5 m/s speed spent 21.2 days and $84, 800/year; and patients with 0.25 m/s speed spent 40.2 days and $160, 800/year. Conclusions: Frailty as measured by gait speed is an independent and potentially modifiable risk factor for cirrhosis complications requiring hospitalization. The potential clinical value of frailty measurements to help define such risk merits broader evaluation.